A rapid and efficient strategy for combinatorial repression of multiple genes in Escherichia coli - Yi Zheng; Yuxia Mo; Yingbo Yuan; Tianyuan Su; Qingsheng Qi (Microbial Cell Factories)
Abstract Background The regulation of multiple gene expression is pivotal for metabolic engineering. Although CRISPR interference (CRISPRi) has been extensively utilized for multi-gene regulation, the construction of numerous single-guide RNA (sgRNA) expression plasmids for combinatorial regulation remains a significant challenge. Results In this study, we developed a combinatorial repression system for multiple genes by optimizing the expression of multi-sgRNA with various inducible promoters in Escherichia coli. We designed a modified Golden Gate Assembly method to rapidly construct the sgRNA expression plasmid p3gRNA-LTA. By optimizing both the promoter and the sgRNA handle sequence, we substantially mitigated undesired repression caused by the leaky expression of sgRNA. This method facilitates the rapid assessment of the effects of various inhibitory combinations on three genes by simply adding different inducers. Using the biosynthesis of N-acetylneuraminic acid (NeuAc) as an example, we found that the optimal combinatorial inhibition of the pta, ptsI, and pykA genes resulted in a 2.4-fold increase in NeuAc yield compared to the control. Conclusion We anticipate that our combinatorial repression system will greatly simplify the regulation of multiple genes and facilitate the fine-tuning of metabolic flow in the engineered strains.